2015
DOI: 10.1177/0956797615569355
|View full text |Cite
|
Sign up to set email alerts
|

Physical Experience Enhances Science Learning

Abstract: Three laboratory experiments involving students' behavior and brain imaging and one randomized field experiment in a college physics class explored the importance of physical experience in science learning. We reasoned that students' understanding of science concepts such as torque and angular momentum is aided by activation of sensorimotor brain systems that add kinetic detail and meaning to students' thinking. We tested whether physical experience with angular momentum increases involvement of sensorimotor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
173
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(213 citation statements)
references
References 20 publications
14
173
2
4
Order By: Relevance
“…The lowest accuracies at pre-test and the greatest improvement at post-test were observed for questions where the balanced object was asymmetric, the system CoG was at a different location from the extended object CoG, and participants were asked to identify the balance point, or the location of the fulcrum or disk that would allow the extended object to balance. Prior research comparing embodied experience with observational experience in learning concepts related to angular momentum suggests that the gain in learning specifically due to embodied activities may be observed only for these more challenging questions [7]. Several factors pose challenges for making a clean comparison between the hands-on and embodied experiences in this study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The lowest accuracies at pre-test and the greatest improvement at post-test were observed for questions where the balanced object was asymmetric, the system CoG was at a different location from the extended object CoG, and participants were asked to identify the balance point, or the location of the fulcrum or disk that would allow the extended object to balance. Prior research comparing embodied experience with observational experience in learning concepts related to angular momentum suggests that the gain in learning specifically due to embodied activities may be observed only for these more challenging questions [7]. Several factors pose challenges for making a clean comparison between the hands-on and embodied experiences in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Applying similar ideas to physics education, a recent study [7] showed that students' understanding of the concepts of torque and angular momentum improved when students physically experienced the consequences of changing angular momentum by tilting the axle of a double bicycle wheel under various configurations, compared with students who observed the exercise and received visual information. In addition, functional Magnetic Resonance Imaging (fMRI) data for participants who had direct experience feeling the associated torque instead of observing forces being exerted on someone else showed activation of sensorimotor brain areas when they later applied these concepts within a scanner [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a few neuroimaging studies have investigated learning directly related to physics and engineering knowledge (Kontra, Lyons, Fischer, & Beilock, 2015;Mason & Just, 2015. One of these studies (Mason & Just, 2015) examined successive stages of learning from lessons about the mechanical properties of a set of four mechanical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Sokoloff et al used active methods to enhance physics laboratories [9]. Kontra et al confirm that interacting with physical items improves learning [10]. One important feature of this project was the focus on making sure each student is active in learning.…”
Section: Introductionmentioning
confidence: 99%